EFEKTIVITAS PENYULUHAN OLEH UNIT BINTIBMAS GUNA MENCEGAH TINDAK PIDANA PENIPUAN ONLINE DI POLRESTA BOGOR KOTA - Aldwi, Muhammad Aldwi Ashary (Police Studies Review, 2020)
This research aims to describe the effectiveness of counseling by Unit Bintibmas Polrestas Bogor Kota in the prevention of criminal acts of online fraud, influencing factors, as well as the effort to overcome obstacles.The approach to this research is qualitative and the kind of research is field research. The data source comes from the primary data and secondary data. Primary Data is obtained through interviews to the sources of Polresta, religious figures, religious figures, students, and perpetrators, acquired in purposive. Secondary Data is obtained through both offline and online documentation. Methods of collecting data using interviews and documentation. Data validity using triangulation method and triangulation theory. Data is then analyzed qualitatively.The results of the research is the effectiveness of the extension by the Bintibmas police Unit Bogor City in the prevention of criminal acts online fraud is not maximal yet effective enough, which is demonstrated by the amount of counseling already according to the work plan, quality of counseling is quite good, and effective enough to improve knowledge and community participation; Supporting factors: Organizational structure (clear organizational structure and leadership), reward, SOP, policies/programs that synergize, and community support (some communities join in Binmas target); The inhibitory factor: quantity and quality of human Resources Limited (high school majority education, training is not routine and less as needed), limited facilities and infrastructures, counseling activities are conducted as needed and incidental despite planning, and perception of society and culture; The efforts of Polresta Bogor city in overcoming obstacles is to optimize budgets, human resources, and social media.Research advice is to improve the quantity and quality of counseling, additional budget as well as facilities and infrastructure, cross-sectoral and intensive cooperation convey the messages of the kamtibmas through social media. Keywords: effectiveness, extension, Bintibmas, online fraud